Stress corrosion cracking in light water reactors : good practices and lessons learned. - Kang, K-S; Kupca, L. (IAEA nuclear energy series ;, 2011)
"The average operating age of existing nuclear power plants (NPPs) is increasing and safety and performance of these ageing NPPs must be achieved by effectively managing material degradations within an acceptable level. Stress corrosion cracking (SCC) is one of significant material degradations for major components of both pressurized water reactors (PWRs) and boiling water reactors (BWRs) and is still an important outstanding technical issue. This publication provides general descriptions of degradation mechanisms of different types of SCC which are concerned to systems, structures and components (SSCs) in PWR and BWR. It includes examples of good practices in preventing, mitigating and repairing SCC damages and summarizes related national and international research and development programmes. Practical operational experience and practices in Member States are also presented in this overview"--Provided by publisher.